Re-purposing is needed for beneficial bugs, not for the drugs - Ram, Hari; Dastager, Syed G. (International Microbiology, 2019)
Between 150 and 200 species of plants, insects, birds or mammals go extinct every day. We do not have any idea what the global extinction rate for microorganisms is. What is clear is that we have already lost a maximum number of the microbes that used to live in and on our skins. Many of our microbial partners are facing extinction as we apply selection pressures that are unprecedented in our long-standing relationships. Recent estimates are that we have lost at least one third of the diversity of our skin microbiome. Every day, most of us bath or shower in water that contains chlorine or fluorine; these additives do a great job of killing pathogenic microbes, but they are probably not helping our skin microbiome. Most of the people apply cosmetic products every day, as these products contain preservatives that prevent microbial growth on the shelf. These same chemicals may well kill microbes on the skin. The daily use of high-pH soaps probably will not help microbial life that is adapted to living on the skin's natural pH of 5. The rise in the rate of C-section births from around 5% in 1970 to more than 30% today is likely to be a contributing factor. Vaginal microbes seed our skins at birth and C-sections disrupt this process. The overuse of broad-spectrum antibiotics has contributed to the loss of our microbial partners in all body sites and the skin is no exception. It is now clear that skin is an ecosystem that is dependent on commensal microbes for optimal health. In general, a diverse ecosystem is a healthy ecosystem that is robust in the face of change. Low-diversity ecosystems are more fragile and susceptible to dysbiosis. Eczema and acne rates have increased rapidly over the last 50 years. These diseases are almost unknown in hunter-gatherer communities. Now, we face two exciting challenges: finding out which species matter and how to get them back.
Keywords: Drugs; Dysbiosis; Microbiome; Probiotics

Probiotics in the prophylaxis of COVID-19: something is better than nothing - Gohil, Kushal; Samson, Rachel; Dastager, Syed; Dharne, Mahesh (3 Biotech, 2021)
The new viral pandemic of COVID-19 is caused by a novel coronavirus (SARS-CoV-2) that has brought the world at another unprecedented crisis in terms of health and economy. The lack of specific therapeutics necessitates other strategies to prevent the spread of infection caused by this previously unknown viral etiological agent. Recent pieces of evidence have shown an association between COVID-19 disease and intestinal dysbiosis. Probiotics comprise living microbes that upon oral administration benefit human health by reshaping the composition of gut microbiota. The close kinship of the gastrointestinal and respiratory tract suggests why the dysfunction of one may incite illness in others. The emerging studies suggest the capability of probiotics to regulate immune responses in the respiratory system. The efficacy of probiotics has been studied previously on several respiratory tract viral infections. Therefore, the purpose of this review is to comprehend existing information on the gut mediated-pulmonary immunity conferred by probiotic bacteria, in the course of respiratory virus infections and administration as a prophylactic measure in COVID-19 pandemic in managing intestinal dysbiosis as well.
Keywords: Anti-viral; COVID-19; Gut-lung axis; Probiotics; Respiratory tract infection

COVID-19 associated mucormycosis: evolving technologies for early and rapid diagnosis - Samson, Rachel; Dharne, Mahesh (3 Biotech, 2022)
The post-coronavirus disease (COVID-19) mucormycosis is a deadly addition to the pandemic spectrum. Although it's a rare, aggressive, and opportunistic disease, the associated morbidity and mortality are significant. The complex interplay of factors aggravating CAM is uncontrolled diabetes, irrational and excessive use of antibiotics, steroids, and an impaired immune system. Recently, India has been witnessing a rapid surge in the cases of coronavirus disease-associated mucormycosis (CAM), since the second wave of COVID-19. The devastating and lethal implications of CAM had now become a matter of global attention. A delayed diagnosis is often associated with a poor prognosis. Therefore, the rapid and early diagnosis of infection would be life-saving. Prevention and effective management of mucormycosis depend upon its early and accurate diagnosis followed by a multimodal therapeutic approach. The current review summarizes an array of detection methods and highlights certain evolving technologies for early and rapid diagnosis of CAM. Furthermore, several potential management strategies have also been discussed, which would aid in tackling the neglected yet fatal crisis of mucormycosis associated with COVID-19.
Keywords: Biosensors; COVID-19; Diagnostics; Mucormycosis; Probiotics